Extracellular Vesicles From Liver Progenitor Cells Downregulates Fibroblast Metabolic Activity and Increase the Expression of Immune-Response Related Molecules - Royo, Felix; Azkargorta, Mikel; Lavin, Jose L.; Clos-Garcia, Marc; Cortazar, Ana R.; Gonzalez-Lopez, Monika; Barcena, Laura; del Portillo, Hernando A.; Yáñez-Mó, María; Marcilla, Antonio; Borras, Francesc E.; Peinado, Hector; et al. (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) mediate cell-to-cell crosstalk whose content can induce changes in acceptor cells and their microenvironment. MLP29 cells are mouse liver progenitor cells that release EVs loaded with signaling cues that could affect cell fate. In the current work, we incubated 3T3-L1 mouse fibroblasts with MLP29-derived EVs, and then analyzed changes by proteomics and transcriptomics. Results showed a general downregulation of protein and transcripts expression related to proliferative and metabolic routes dependent on TGF. We also observed an increase on the ERBB2 interacting protein (ERBIN) and Cxcl2, together with an induction of ribosome biogenesis and interferon-related response molecules suggesting the activation of immune system signaling.